Design And Implementation Of Shahed Buildings\' Campus Network - Khalilabad, Hadi Nejatian (2007)
This project tries to identify the feasibility for a campus LAN for Data Communication Company of Iran\'s Shahed buildings (DCI). The Campus Network Design for DCI\'s Shahed buildings is sort of an all-in-one guide to switched Ethernet design that bedside explaining about designing the campus networks for DCI, instructs readers on key LAN infrastructure components.